Troubling school toilets: resisting discourses of 'development' through a critical disability studies and critical psychology lens. Issue 3 (4th May 2019) - Slater, Jen; Jones, Charlotte; Procter, Lisa
ABSTRACT: This paper interrogates how school toilets and 'school readiness' are used to assess children against developmental milestones. Such developmental norms both inform school toilet design and practice, and perpetuate normative discourses of childhood as middle-class, white, 'able', heteronormative, cissexist and inferior to adulthood. Critical psychology and critical disability studies frame our analysis of conversations from online practitioner forums. We show that school toilets and the norms and ideals of 'toilet training' act as one device for Othering those who do not fit into normative Western discourses of 'childhood'. Furthermore, these idealised discourses of 'childhood' reify classed, racialised, gendered and dis/ablist binaries of good/bad parenting. We conclude by suggesting new methodological approaches to school toilet research which resist perpetuating developmental assumptions and prescriptions. In doing this, the paper is the first to explicitly bring school toilet research into the realms of critical psychology and critical disability studies.